2014
DOI: 10.1002/acr.22214
|View full text |Cite
|
Sign up to set email alerts
|

Current Evidence of Anti–Tumor Necrosis Factor α Treatment Efficacy in Childhood Chronic Uveitis: A Systematic Review and Meta‐Analysis Approach of Individual Drugs

Abstract: Objective. To summarize evidence regarding the effectiveness of anti-tumor necrosis factor ␣ (anti-TNF␣) treatments in childhood autoimmune chronic uveitis (ACU), refractory to previous disease-modifying antirheumatic drugs (DMARDs). Methods. A systematic search between January 2000 and October 2012 was conducted using EMBase, Ovid Medline, Evidence-Based Medicine (EBM) Reviews: American College of Physicians Journal Club, Cochrane libraries, and EBM Reviews. Studies investigating the efficacy of anti-TNF␣ the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
2
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 46 publications
3
75
2
8
Order By: Relevance
“…However, in neither study was it possible to extract specific outcomes in the subset of patients who received ADA as first-line biologic treatment. In a metaanalysis including 5 studies of ADA, improvement in intraocular inflammation was reported in 87% of 31 patients with JIA, but again, the number of biologics-naive patients was not specified, and data on remission were available only for a few cases 9 . The only available study in which ADA was …”
Section: Discussionmentioning
confidence: 99%
“…However, in neither study was it possible to extract specific outcomes in the subset of patients who received ADA as first-line biologic treatment. In a metaanalysis including 5 studies of ADA, improvement in intraocular inflammation was reported in 87% of 31 patients with JIA, but again, the number of biologics-naive patients was not specified, and data on remission were available only for a few cases 9 . The only available study in which ADA was …”
Section: Discussionmentioning
confidence: 99%
“…Etanercept is not recommended Legend: bd twice daily, GI gastro-intestinal, od once daily, po by mouth, sc subcutaneous in patients with JIA-U. A meta-analysis including 229 children with JIA-U has shown that infliximab and adalimumab have similar efficacy and both are superior to etanercept [61]. However, during 40 months' follow-up, uveitis more commonly remained in remission in those treated with adalimumab compared with infliximab (60 % vs 18.8 % respectively) [62].…”
Section: Biologic Drugsmentioning
confidence: 99%
“…A recently published systematic review by Simonini and colleagues 96 assessed the effectiveness of antiTNF drugs for childhood uveitis. To be included, studies had to include patients with autoimmune uveitis refractory to topical and/or systemic steroids and at least one immunosuppressive therapy (e.g.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…The registry does not appear to include patients from the UK. Other evidence such as case series, open-label trials, a systematic review 96 and data from an Italian registry were included to provide evidence for the effectiveness of adalimumab in JIA-associated uveitis (see JIA-associated uveitis of this assessment report for details of these).…”
Section: Review Of Abbvie Company Evidence Submission For Adalimumabmentioning
confidence: 99%